Cell-Autonomous Expression of Barley Mla1 Confers Race-Specific Resistance to the Powdery Mildew Fungus via a Rar1-Independent Signaling Pathway - Zhou, Fasong (American Society of Plant Physiologists, 2001)
The barley Mla locus encodes 28 characterized resistance specificities to the biotrophic fungal pathogen barley powdery mildew. We describe a single-cell transient expression assay using entire cosmid DNAs to pinpoint Mla1 within the complex 240-kb Mla locus. The MLA1 cDNA encodes a 108-kD protein containing an N-terminal coiled-coil structure, a central nucleotide binding domain, and a C-terminal leucine-rich repeat region; it also contains a second short open reading frame at the 5′ end that has a possible regulatory function. Although most Mla-encoded resistance specificities require Rar1 for their function, we used the single-cell expression system to demonstrate that Mla1 triggers full resistance in the presence of the severely defective rar1-2 mutant allele. Wheat contains an ortholog of barley Mla, designated TaMla, that is tightly linked to (0.7 centimorgan) but distinct from a tested resistance specificity at the complex Pm3 locus to wheat powdery mildew. Thus, the most polymorphic powdery mildew resistance loci in barley and wheat may have evolved in parallel at two closely linked homeoloci. Barley Mla1 expressed in wheat using the single-cell transformation system failed to trigger a response to any of the wheat powdery mildew Avr genes tested, indicating that AvrMla1 is not genetically fixed in wheat mildew strains.